Deforestation Analysis in Taba Penanjung District with NDVI - Vatresia, Arie; Utama, Ferzha Putra; Rais, Rendra Regen; Prasetyo, Bimo (Universitas Sriwijaya, 2022)
Forests are cleared to expand residential areas and plantations or change the allocation of forest land to non-forest (deforestation). This study aims to create a map of the condition of the forest area and find out the areas affected by deforestation and determine the rate of change in the forest area in the Taba Penanjung District forest area. First data on Landsat 8 images geometric correction performed to position image data so that it matches the actual coordinates and performing Radiometric Correction is used to correct if an error or distortion occurs due to imperfect operation and sensors. NDVI Method is the method used for comparing the greenness of vegetation in satellite imagery, which uses band 4 (Red) and band 5 (NIR), which is processed by ArcMap software. The results of this study produced a map of the condition of forest areas and the area of land affected by deforestation. Forest turn-over rates were described in the annual trend from 2013 to 2018. Furthermore, this research shows that deforestation in the Taba Penanjung district has happened in 58% of the total area of 23, 747 ha. Although the deforestation has decreasing value in 2015 by 1.6%, it showed that there were increasing values in deforestation rate in 2014, 206, 2017 by 1.4%, 1.9%, and 9.5% respectively from the total area of 23, 747 ha.